Raising Arizona [videorecording (Blu-Ray)] - Coen, Joel; Coen, Ethan; Cage, Nicolas, 1965-; Hunter, Holly, 1958-; Wilson, Trey; Goodman, John, 1952-; Forsythe, William, 1955-; McMurray, Sam; McDormand, Frances; Cobb, Randall, 1950-; Sonnenfeld, Barry; Burwell, Carter (Twentieth Century Fox Home Entertainment, 2011)
Once he decides to give up crime, a small-time robber proposes to a pretty cop. But when the newlyweds learn they can't conceive a baby, they decide to steal one from a couple who seem to have one to spare, since they just had quintuplets!